Contractors’ participation in sustainable construction / Mohamed Rizal Mohamed, Siti Akhtar Mahayuddin and Noor Rizallinda Ishak - Mohamed, Mohamed Rizal; Mahayuddin, Siti Akhtar; Ishak, Noor Rizallinda (2012)
Construction activities consume high quantity of natural resources which give negative impact to the environment. Contractors are directly involved in these activities. Therefore, they are responsible to minimize this negative impact apart from maximizing their economic contribution. Based on literature reviews, this paper presents three aspects of contractors’ participation in sustainable construction, which are improving the efficiency of the construction process, conserving energy, water, and other resources during construction and minimizing the amount of construction waste.Contractors should realize the importance of improvement of their sustainable performance in order to improve their business. In conclusion, contractors need to take serious actions for planning and managing their construction work with regards to minimize the environmental impacts related to the construction process.